The behaviour of Tollmien-Schlichting waves undergoing small-scale localised distortions - Xu,H; Sherwin,S; Hall,P; Wu,X (Journal of Fluid Mechanics, 2016)
This paper is concerned with the behaviour of Tollmien-Schlichting (T-S) waves experiencingsmall localised distortions within an incompressible boundary layer developingover a flat-plate. In particular, the distortion is produced by an isolated roughness elementlocated at Rexc = 440 000. We considered the amplification of an incoming T-S wavegoverned by the two-dimensional linearised Navier-Stokes equations, where the base flowis obtained from the two-dimensional non-linear Navier-Stokes equations. We comparethese solutions with asymptotic analyses which assume a linearised triple-deck theory forthe base flow and determine the validity of this theory in terms of the height of the smallscalehumps/indentations taken into account. The height of the humps/indentations isdenoted by h which is considered to be less than or equal to xcRe−5/8xc(correspondingto h/δ99 < 6% for our choice of Rexc). The rescaled width ˆd(≡ d/(xcRe−3/8xc)) ofthe distortion is of the order O(1) and the width d is shorter than the T-S wavelength(λT S = 11.3 δ99).We observe that for distortions which are smaller than 0.1 of the inner deck height(h/δ99 < 0.4%) the numerical simulations confirm the asymptotic theory in the vicinityof the distortion. For larger distortions which are still within the inner deck (0.4% <h/δ99 < 5.5%) and where the flow is still attached the numerical solutions show thatboth humps and indentations are destabilising and deviate from the linear theory evenin the vicinity of the distortion.We numerically determine the transmission coefficient which provides the relative amplificationof the T-S wave over the distortion as compared to the flat-plate. We observethat for small distortions, h/δ99 < 5.5%, where the width of the distortion is of orderof the boundary layer a maximum amplification of only 2% is achieved. This amplificationcan however be increased as the width of the distortion is increased or